From nanohole to ultralong straight nanochannel fabrication in graphene oxide with swift heavy ions - Andrzej Olejniczak; Ruslan A. Rymzhanov (Nature Communications, 2023)
While porous graphene oxide with nm-sized pores can be of great interest to biofluidic and energy storage applications, achieving precisely controlled porosity remains a technical challenge. Here, the authors exploit swift heavy ions to create uniform nanoholes and ultralong straight nanochannels in GO films.